Phase I study of carfilzomib, lenalidomide, vorinostat, and dexamethasone in patients with relapsed and/or refractory multiple myeloma. (27th May 2015) - Vesole, David H.; Bilotti, Elizabeth; Richter, Joshua R.; McNeill, Ann; McBride, Laura; Raucci, Laura; Anand, Palka; Bednarz, Urszula; Ivanovski, Kristin; Smith, Judith; Batra, Veena; Aleman, Adolfo; et al.
Summary Research has shown that proteasome inhibitors (e.g., carfilzomib), immunomodulatory agents (e.g., lenalidomide), histone deacetylase inhibitors (e.g., vorinostat) and corticosteroids (e.g., dexamethasone) have synergistic anti‐multiple myeloma (MM) activity. This phase I dose‐escalation study evaluated a regimen combining carfilzomib, lenalidomide, vorinostat and dexamethasone (QUAD) in patients with relapsed and/or refractory MM. Seventeen patients received carfilzomib (15, 20, or 20/27 mg/m2; 30‐min infusion; days 1, 2, 8, 9, 15, 16), lenalidomide (15 or 25 mg; days 1–21), vorinostat (300 or 400 mg; days 1–7, 15–21), and dexamethasone (40 mg; days 1, 8, 15, 22) in 28‐d cycles. No dose‐limiting toxicities were observed; the maximum tolerated dose was not reached. The maximum administered dose was carfilzomib 20/27 mg/m2, lenalidomide 25 mg, vorinostat 400 mg, and dexamethasone 40 mg. Common grade ≥3 adverse events included neutropenia (53%), thrombocytopenia (53%) and anaemia (41%). The overall response rate was 53%: 12% of patients achieved a very good partial response (PR) and 41% of patients achieved a PR. At a median follow‐up of 10 months, median progression‐free survival was 12 months and median overall survival was not reached. Treatment with QUAD was feasible and had encouraging activity in patients with relapsed and/or refractory MM.